COT-17 EFFECT OF BEVACIZUMAB AGAINST CYSTIC COMPONENT OF PRIMARY/METASTATIC BRAIN TUMORS. (16th December 2019) - Yamasaki, Fumiyuki; Takano, Motoki; Yonezawa, Ushio; Taguchi, Akira; Onishi, Shumpei; Kurisu, Kaoru; Sugiyama, Kazuhiko
Abstract: BACKGROUND: Bevacizumab (BEV) improves the symptom via reducing the peritumoral edema and sometimes via reducing the size of brain tumor. However, the effect of BEV against cystic part of brain tumor has not been documented yet. In this report, we investigated the effect of BEV on cystic component of brain tumors. MATERIALS AND METHODS: Our institutional review board approved this retrospective study. Between 2008 and 2018, 139 patients with primary or metastatic brain tumor were treated with BEV in our Hospital. We defined cystic lesions as high intense lesion of size 1 cm or bigger on T2WI, and excluded necrotizing cysts and cystic changes in surgical resection cavity. The symptoms and images before and after administration of bevacizumab were evaluated. Changes in cyst size of brain tumor was evaluated as follows: CR (complete response=disappearance), PR (reduction by 50% or more), MR (reduction by 25–50%), SD (size change less than 25%), PD (increase by 25% or more). The effect of bevacizumab on tumor itself was determined according to RANO criteria. RESULTS: Of the 139 patients, 21 (15.1%) brain tumors had cystic component. The best response of cyst to BEV were as follows: CR 6, PR 7, MR 4, SD 4. The group of patients with progressively increasing cysts prior to BEV administration had significant cyst size reduction compared to stable cyst size groups at best response timing (mean 76.3% vs. 32.8%, P<0.01). Patients with cyst showed significant improvement of symptoms after the treatment with BEV compared to patients without cyst (P<0.01). However, response rate against tumor itself was not different between patients with or without cyst. Overall survival of glioblastoma patients after starting BEV was not different between tumor with cyst and without cyst. CONCLUSION: BEV may be effective for patients who are symptomatic due to cystic enlargement.